CHEWTOPIA : a visual communication exploration of positioning Teochew culture for a contemporary audience - Quek, Amanda Wei Yi (2015)
The slow death of Chinese dialects over the past decades, largely attributed to language policies put in place by the Singapore government, has resulted in many of the younger generations losing the ability to speak their own cultural dialect and consequently the understanding of their own cultural heritage. This growing lack of understanding coupled with the missed opportunities that come together with a fading cultural language has led to a general decline in attitudes towards the valuing and caring of our own cultural roots. This project aims to explore and identify a solution that might position the Teochew culture in a manner that is relevant to contemporary Singapore in an immersive and engaging way; so as to encourage younger Singaporean Teochews to take heart and pride in the understanding, caring for and eventual preserving of their own culture. To do so, a theme park was created to appeal to the younger fun-seeking generation. The theme park includes many different features of the Teochew culture, such as the architecture, lifestyle and history, which are presented to the younger generation in the form of, rides, mazes and even at the cafes. Through the theme park journey and the features created within in, it aims to narrate the Teochew culture in an engaging way that is relevant to a contemporary audience.